The Controversies over State Secularism in the Constitution of the 4th Republic of Madagascar - Ramahefarivo, Rota Ranavalonatina (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2022)
The first article of the 4th Republic of Madagascar states that Madagascar is a secular State. However, there are many controversies related to this secularism. Those controversies are both textual and empirical. In reality Madagascar is not a pure secular State. This article consist of explaining the cause of the contradiction of secularism found in the content of the Constitution and the reality. The objective of this study is to describe the controversies about the application of the secularism principle during the 4th Republic and especially under the regime of the President Andry Rajoelina. If the Constituent think the concept of secularism as western countries think, especially France, Madagascar has its own way of application, because of the influence of traditional belief and Christianism. Then, the existence of a contextual secularism will be the solution for the controversies.